Geocronologia 40AR/39AR das rochas e evolução mineralógica e geoquímica do manto de intemperismo do complexo alcalino-carbonatítico de Tapira (MG) - Godoy, Letícia Hirata [UNESP] (2015)
In this work the geochronology of the rocks and a mineralogical and geochemical characterization of the weathering cover was performed in the Tapira alkaline-carbonatitic complex, Minas Gerais State, Brazil, which belongs to The Alto Parnaíba Igneous Province (APIP). The rocks can be grouped in the silicate (bebedourites and syenites), carbonatitic and foscoritic series, and the thick weathering cover above them can be divided in poor phosphatic zone, phosphatic zone, titanium zone, deep cover and superficial cover. The concentration of major and minor elements varies according to the lithotype and mineralogical content or according to the weathering state of the sample and, therefore the neoformed mineral phases. The geochemical analysis indicates that the magmatism, which generated Tapira rocks, is associated with a metasomatically enriched lithosphere melting. Moreover, the weathering processes are typically related to partial hydrolysis of silicatic rocks and dissolution of carbonates, with a general loss of Ca, Mg, K and Si, and accumulation of Al, Fe and Ti. The distribution patterns of REE in the bebedourites, foscorite and syenite samples, possibly indicate the same magmatic source for these rocks. The content in REE increases from the fresh rock towards the titanium zone, probably due to a rapid reprecipitation of the REE and to the lost of major elements that are easily remobilized during the chemical weathering progression. In the deep and superficial covers, the concentration of REE decreases towards the top of the profiles, along with an increase in SiO2 and Al2O3 concentrations, probably due to the influence of country-rocks materials that were incorporated by the end of the weathering and denudation processes. The new 40Ar/39Ar ages indicate three magmatic events during the emplacement of this complex in ca. 96 Ma, 85-86 Ma and 79 ... (Complete abstract click electronic access below)